2014
DOI: 10.3389/fneur.2014.00228
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Electro- and Magneto-Encephalography in Tinnitus Research – Methods and Interpretations

Abstract: In recent years, there has been a significant increase in the use of electroencephalography (EEG) and magnetoencephalography (MEG) to investigate changes in oscillatory brain activity associated with tinnitus with many conflicting results. Current view of the underlying mechanism of tinnitus is that it results from changes in brain activity in various structures of the brain as a consequence of sensory deprivation. This in turn gives rise to increased spontaneous activity and/or synchrony in the auditory cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 198 publications
2
48
0
Order By: Relevance
“…We are well-aware, that not all of these suggestions have the same gravity in regards to source estimation and diverging results across studies, yet are convinced that also minor differences may influence results as in tinnitus research weak effects, nil findings and irreconcilable results are omnipresent. Finally, while not directly addressing the methodological comparison of the two studies but general validity of the applied source estimation, limitations of the method should be considered and properly discussed (Adjamian, 2014). Of central interest here, we identify the fact the standardized boundary element method volume conductor model behind the LORETA algorithm (Fuchs et al, 2002) is based on a standardized MNI brain template derived from a young, healthy cohort in their mid-twenties, which generally contrasts the mean age of the samples used in tinnitus studies (mean=42.78 years, in our study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are well-aware, that not all of these suggestions have the same gravity in regards to source estimation and diverging results across studies, yet are convinced that also minor differences may influence results as in tinnitus research weak effects, nil findings and irreconcilable results are omnipresent. Finally, while not directly addressing the methodological comparison of the two studies but general validity of the applied source estimation, limitations of the method should be considered and properly discussed (Adjamian, 2014). Of central interest here, we identify the fact the standardized boundary element method volume conductor model behind the LORETA algorithm (Fuchs et al, 2002) is based on a standardized MNI brain template derived from a young, healthy cohort in their mid-twenties, which generally contrasts the mean age of the samples used in tinnitus studies (mean=42.78 years, in our study).…”
Section: Discussionmentioning
confidence: 99%
“…However, we favor neurophysiological M/EEG techniques in the context of tinnitus research because these approaches are not accompanied by bothersome gradient noise and hence are more comfortable for TI, who often show symptoms of hyperacusis. Further, comprehensive leaps have been made to improve the spatial resolution of M/EEG through the development of innovative source estimation approaches (Adjamian, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a clear distinction of similarities and dissimilarities between the tinnitus and non-tinnitus brain has yet to be identified, as findings have not been consistent across studies (Elgoyhen et al 2015;Güntensperger et al 2017). Potential reasons for the discrepancies in oscillatory findings are manifold, and may include differences in study design and sample selection; technique-and analysis-specific aspects (Adjamian 2014;Gross et al 2013;Meyer et al 2017); biological factors such as age (Schlee et al 2012), tinnitus duration (Schlee et al 2009), and degree of hearing loss (Adjamian et al 2012); comorbidities such as hyperacusis, sleep disorders, headache, and concentration problems (Zirke et al 2010); and associated psychopathological symptoms such as tinnitus-related distress and depression, which contribute their own levels of oscillatory correlates. Along these lines, Meyer et al conducted a study that was explicitly designed to re-enact a former EEG resting-state experiment (Joos et al 2012;Meyer et al 2017).…”
Section: A Brief Digression: Tinnitusmentioning
confidence: 99%
“…Diagnosing tinnitus is difficult, because the condition may not be detected using objective methods. Attempts have been made to address this problem using brain imaging modalities, such as functional magnetic resonance imaging and electroencephalometry . These modalities have demonstrated that tinnitus patients show modulated brain activity in nonauditory centers, such as limbic, paralimbic, and even frontal areas, as well as in the auditory centers .…”
Section: Introductionmentioning
confidence: 99%